Introduction of a natural resource balance indicator to assess soil organic carbon management: Agricultural Biomass Productivity Benefit. (15th October 2018) - Boone, Lieselot; Van linden, Veerle; Roldán-Ruiz, Isabel; Sierra, Carlos A.; Vandecasteele, Bart; Sleutel, Steven; De Meester, Steven; Muylle, Hilde; Dewulf, Jo
Abstract: The rising demand for feed and food has put an increasing pressure on agriculture, with agricultural intensification as a direct response. Notwithstanding the higher crop productivity, intensive agriculture management entails many adverse environmental impacts. Worldwide, soil organic carbon (SOC) decline is hereby considered as a main danger which affects soil fertility and productivity. The life cycle perspective helps to get a holistic overview when evaluating the environmental sustainability of agricultural systems, though the impact of farm management on soil quality aspects is often not integrated. In this paper, we introduce an indicator called Agricultural Biomass Productivity Benefit of SOC management (ABB_SOC), which, relying on natural resource consumption, enables to estimate the net effect of the efforts made to attain a better soil quality. Hereby the focus is put on SOC. First, we introduce a framework to describe the SOC trend due to farm management decisions. The extent to which remediation measures are required are used as a measure for the induced SOC losses. Next, ABB_SOC values are calculated as the balance between the natural resource consumption of the inputs (including remediation efforts) and the desired output of arable crop production systems. The models RothC and EU-Rotate_N are used to simulate the SOC evolution due to farm management and the response of the biomass productivity, respectively. The developed indicator is applied on several rotation systems in Flanders, comparing different remediation strategies. The indicator could be used as a base for a method to account for soil quality in life cycle analysis. Graphical abstract: Image 1 Highlights: A framework to assess impacts of soil organic carbon (SOC) management is developed. Changes in SOC stock are quantitatively related to biomass productivity. A natural resource accounting approach is used to develop a sustainability indicator. The proposed indicator accounts for land use efficiency of arable crops. The indicator is proven useful to assess SOC remediation options and crop rotations.